HEADACHE PROFILE OF BRAIN TUMOR PATIENTS IN MOHAMMAD HOESIN HOSPITAL PALEMBANG - Yunni Diansari; Henry Sugiharto; Sheila Stephanie Chandra (Majalah Kedokteran Sriwijaya, 2022)
Background: Headache is one of the most common complaint in population while a serious causative of underlying disease is very rare. Although headaches are rarely the result of a brain tumor, brain tumors are frequently associated with headaches. The challenges to the physician are to determine the specific feature of headache related to brain tumor.Methods: This is cross sectional study involved primary and metastatic brain tumor patient admitted in neurology ward of Mohammad Hoesin hospital from April 2018 to June 2019. The inclusion criteria including age > 18 years old and there was symptom of headache based on anamnesis. All were interviewed about their personal details (age, gender). The characteristic of headache was obtained based on questionnaire designed in our department. Various neurological symptoms related to the tumor were also recorded. Information of the tumor was obtained from the patient’s chart (histopathology of the tumor) and from characteristic of neuroradiological finding (magnetic resonance imaging or computed tomography). Headache and tumor characteristics were compared between primary and metastatic tumor by contrasting frequencies. We also analysed the correlation between tumor characteristics (location, hidrocephalus, vasogenic edema and tumor type) with headache intensity.Results: A total of 95 of 199 patients (48%) with headache symptom were studied in this series. Most patients were complained of chronic headache. Headache was mostly throbbing in both primary and metastatic brain tumors.  Progressively headache was dominant in this study and more than half patients report the quality of headache as moderate at the onset. In 35,8% patients, headache was the patient’s first complaint.  Headache as the isolated symptom of brain tumor was found in only 3,2% and only 28,4% of patients ful?lled the three ‘classic criteria’ of the brain tumor headache. A great localizing value of the headache was found in 63 cases of 95 patients. Of the 61 patients with single tumor and unilateral side, the unilateral headache was on 48 cases (78,8%). Of the 26 patients with strictly bilateral headache, 10 cases (38,5%) had bilateral sided tumors. Conclusion: The incidence of brain tumor headache in this study is similar to previous reports although the classic brain tumor headache features was found in a small portion of the patients.